Construction Of Verb In Ugaritic Language A Comparative Study (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research is done to identify the structures of the verb in Ugaritic Language in a comparative study in Arabic. This study shows that the verb in Ugaritic Language is studied in terms of its derivative “root”, its original characters “abstraction”, its extra characters , suffixes, prefixes and, infix  , its form and metres “inflection”, its syntactic forms  , and its tenses that it indicates. Also this study shows that the verb in Ugaritic Language is studied by looking into its meaning whether it is an intransitive or transitive verb. In addition to study the relations “syntactic functions” in the Ugaritic sentence.